2003
DOI: 10.1021/jp0276193
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of the Phthalimide N-Oxyl (PINO) Radical in Acetic Acid. Hydrogen Abstraction from C−H Bonds and Evaluation of O−H Bond Dissociation Energy of N-Hydroxyphthalimide

Abstract: The reactions of the phthalimide N-oxyl (PINO) radical with several hydrocarbons having different C−H bond dissociation energies (BDEs) were investigated in HOAc at 25 °C. The slope of the Evans−Polanyi plot is 0.38, which indicates that the reactions are mildly exothermic or almost thermoneutral. This finding is supported by the O−H BDE of N-hydroxyphthalimide (NHPI), 375 ± 10 kJ mol-1, obtained by means of a thermodynamic cycle. The observed kinetic isotope effects (KIEs) are related to the reaction free-ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
81
2
7

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 32 publications
16
81
2
7
Order By: Relevance
“…[9,14,15,17,18,25] The contribution from tunnelling is clear, as also documented elsewhere. [14,17] c -Products study for reaction of TFNO with a probe substrate.…”
Section: Scheme 3 Competition Of Et Vs Hat Routes With An Aminoxyl Rsupporting
confidence: 65%
See 1 more Smart Citation
“…[9,14,15,17,18,25] The contribution from tunnelling is clear, as also documented elsewhere. [14,17] c -Products study for reaction of TFNO with a probe substrate.…”
Section: Scheme 3 Competition Of Et Vs Hat Routes With An Aminoxyl Rsupporting
confidence: 65%
“…[14,16,17] Summing it up, the reactivity features of TFNO in the HAT process (Table 2) are akin to those of other aminoxyl radicals, [10] including the finding of an accelerating effect from electron-donor and the retarding effect from electron-withdrawing substituents on the benzylic substrate. Significant figures for this comparison of reactivity among aminoxyl radicals are selected and given in Table 3, proper allowance being made to the different solvents employed (no major effects upon the rates are however expected in these radical processes [14,15,25] ).…”
Section: Characterization Of the Radical Tfnomentioning
confidence: 99%
“…Thus, the rate constant for reaction of HBr 2 · with toluene (in HOAc) is > 10 4 times that for the benzylperoxy radical. [14,35] Variable valence metal ions, such as cobalt and manganese, serve as catalysts of autoxidations by undergoing one electron redox reactions with alkyl hydroperoxides to produce alkoxy and alkylperoxy radicals. [30] The former abstract hydrogen atoms from C À H bonds with a rate constants 10 5 -10 7 larger than for alkylperoxy radicals, [13] a reflection of the much larger BDE of RO À H (437 kJ/mol) compared to ROO À H (370 kJ/mol).…”
Section: Reviewsmentioning
confidence: 99%
“…Two groups [13,14] have recently determined the BDE of the O À H bond in NHPI and mixed acylalkylhydroxylamines (substituted hydroxamic acids), and compared them (see Table 1) with that of the O À H bond in TEMPOH which was already known. [15] The chemistry of nitroxyl radicals was extensively investigated in the 1960s and 1970s by Perkin [16 -19] and others [20] and the higher reactivity of acylalkylnitroxyls …”
Section: Introduction To Nitroxyl Radicalsmentioning
confidence: 99%
“…Nevertheless, A C H T U N G T R E N N U N G (TEMPO) 2 Co(DH) 2 was instable and might decompose to release cobaloxime at the higher temperature. Generally, the O À H of oximes have relatively low bond dissociation energies, [11] meaning that their homolytic cleavage occurs easily. Recently, we have found that at around 80 8C DH 2 could provide efficiently its corresponding N-oxyl radical for oxidation of hydrocarbons.…”
Section: The Catalytic Mechanismmentioning
confidence: 99%